Polycyclic Tetramate Macrolactams—A Group of Natural Bioactive Metallophores - Ding, Ling; Zhang, Sheng-Da; Haidar, Ahmad Kasem; Bajimaya, Manila; Guo, Yaojie; Larsen, Thomas Ostenfeld; Gram, Lone (Frontiers in Chemistry, 2021)
New infectious diseases and increase in drug resistant microbial pathogens emphasize the need for antibiotics with novel mode-of-action. Tetramates represented by fungi-derived tenuazonic acid and bacterial polycyclic tetramate macrolactams (PTMs) are an important family of natural products with a broad spectrum of antimicrobial activities. Despite their potential application as new antibiotics, it remains unknown how PTMs function. In this study, genomic mining revealed that PTM biosynthetic gene clusters (BGCs) are widespread in both Gram positive and Gram negative bacteria. A sponge endosymbiont Actinoalloteichus hymeniacidonis harboring a potential PTM-BGC was investigated in this study. Xanthobaccin A previously reported from only a Gram negative bacterium was obtained after a scale-up fermentation, isolation and structure elucidation through mass spectrometry and nuclear magnetic resonance (NMR) spectroscopy. Xanthobaccin A as well as two previously reported tetramates equisetin and ikarugamycin exhibited antibacterial activities against Bacillus subtilis. In addition, those three tetramates were for the first time to be confirmed as metallophores and the stoichiometry of the complexes are Fe(Ⅲ)(equisetin)3/Fe(Ⅲ)(equisetin)2 and Fe(Ⅲ)(ikarugamycin)2, respectively. Meanwhile, we found that all three tetramates could reduce ferric into ferrous iron, which triggers the Fenton Chemistry reaction. Their antibacterial activity was reduced by adding the radical scavenger vitamin C. Altogether, our work demonstrates that equisetin and PTMs can act as metallophores and their antimicrobial mechanism is possibly mediated through the Fenton Chemistry.